Without fear or favor : a novel - Tanenbaum, Robert (Tanenbaum, Robert. Butch Karp and Marlene Ciampi series., 2017)
"In the twenty-ninth novel in the New York Times bestselling Karp-Ciampi series featuring "the best fictional prosecuting attorney in literature" (Mark Lane, #1 New York Times bestselling author), Butch Karp and his wife Marlene Ciampi must stop a radical organization of armed militants bent on the cold-blooded murder of uniformed on-duty police officers. When a cop shoots down the son of a respected inner-city Baptist preacher, the community rises up in anger and demands to have the officer prosecuted to the fullest extent of the law. But there's something more than a call for justice at work here: a plot to bring down the city's police force through a conspiracy so vast and malicious only Butch Karp and his band of truth-seekers can untangle it. Full of Tanenbaum's signature page turning intense action and heart pounding suspense from "one hell of a writer" (New York Post), Without Fear or Favor will keep you guessing until the final scene"--